Assessment of serum nitrate-nitrite ratio vis-a-vis insulin sensitivity and resistance in type 2 diabetics in a tertiary hospital in Eastern India - Deb, Nayana; Chatterjee, Sharmistha; Mukhopadhyay, Mousumi; Majumder, Biswajit; Bhattacharyya, Swati (International Journal of Research in Medical Sciences, 2016)
Background: Insulin Resistance is of paramount importance in the pathophysiology of Type 2 Diabetes Mellitus along with endothelial dysfunction is mediated by Nitric Oxide (NO). Central to this endothelial dysfunction is the action of Insulin on the Nitric oxide synthase enzyme. Since NO cannot be measured because of its short half-life, metabolites of NO (namely nitrite and nitrate) are measured towards assessing their relationship along with different direct and surrogate markers of insulin resistance in patients of Diabetes Mellitus attending a tertiary care hospital in Eastern India. Aim of the study was to assess the level of Insulin resistance with the direct and surrogate markers of insulin resistance in patients of Diabetes Mellitus attending a tertiary care hospital in Eastern India. Methods: Blood samples from newly diagnosed Type 2 Diabetic patients were assayed for fasting and postprandial sugar and insulin, lipid profile and serum nitrate and nitrite and different anthropological parameters were measured. After that, HOMA-IR and QUICKI’ index were measured. Results: Values of anthropological parameters and the direct and surrogate markers of insulin resistance showed statistically significant difference between cases and controls. Bivariate analysis of post-prandial blood glucose showed strong co-relation with HOMA-IR while serum total nitrate-nitrite ratio showed a strong co-relation with QUICKI. Conclusions: Serum nitrate-nitrite ratio showed a strong co-relation with HOMA-IR and QUICKI. The significance of this study lies in the fact that measurement of the serum nitrate-nitrite may give an idea of the level of insulin resistance of a diabetic patient.